Dental Status and Characteristics of Oral Fluid in Patients with Juvenile Rheumatoid Arthritis (Indian Journal of Public Health Research & Development, 2020)
Changes and disturbances in any human system can be a trigger for the emergence, exacerbation orprogression of diseases of other organs and systems. This is confirmed by modern scientific works thatdemonstrate the dependence of dental status on background pathology. Considering the fact that biofilm ofthe oral cavity can be a risk factor in maintaining a high degree of activity of the underlying disease, as wellas the informativeness of oral fluid indices, studies in this direction seems relevant. Aim of the research isto study the physical and immunohormonal characteristics of oral fluid in patients with juvenile rheumatoidarthritis depending on the duration of arthritis.Materials and Method: A dental examination was conducted on 65 patients with JRA aged 12-16 years(average age 13.55 ± 0.21 years), among whom the debut of arthritis less than 6 years was observed in 32patients (49.23%) and more than 6 years in 33 patients (50.77%). Comparison control group (CG) was 15almost healthy patients. Dental status was assessed by the intensity of the carious process (DMF-index) andthe severity of gingivitis (PMA-index). The productive activity of the OF was characterized by the basicspeed of salivation and saliva viscosity (according to the method of Redinova-Pozdeeva, 1994). The oralfluid was analyzed according to the content of hormones (cortisol, ACTH) and interleukins (IL-1?, IL-6,TNF?, IL-4, IL-10) in accordance with the duration of arthritis.Results and Conclusion: It was found that in patients with juvenile rheumatoid arthritis there is a “high”degree of caries activity, a “mild” degree of gum inflammation, an imbalance in the pituitary-adrenal axishormones and a state of immunosuppression at the local level. At the peripheral level, marked violationsare observed in the principle of regulation of feedback “cortisol-ACTH” and signs of immunodeficiencyaccording to the levels of interleukins were observed. Identified disorders tend to progress with increasingduration of arthritis. These results can be used in the practice of dentists, rheumatologists and pediatricians.
Keywords: Caries, gingivitis, oral fluid, juvenile rheumatoid arthritis